Health care for the obese person in the Intensive Care Unit (ICU) (Research, Society and Development, 2022)
This study focused on discussing health care for obese patients treated in Intensive Care Units (ICU). Therefore, we follow the following objectives, general and specific, respectively: To analyze what are the causes and consequences of obesity; Investigate what are the public policies to combat obesity; To identify in the literature which are the health care to be applied in the care of the obese person. The methodology used to support the research was a narrative literature review and critical analysis of research publications carried out by scholars in the field of knowledge. Conclusion: Through the research carried out, we found that the causes of obesity are inadequate diet, sedentary lifestyle, family genetics, socioeconomic levels, psychological factors, demographic factors, educational level, early weaning, having obese parents, consuming alcohol and being a smoker. It has as consequences the emergence of chronic diseases, such as hypertension, cardiovascular dysfunctions, ischemic strokes, type 2 diabetes mellitus and some types of cancer, such as colorectal, kidney diseases, emotional disorders, low self-esteem and social isolation. In addition, some public policies to combat obesity were developed, such as the Academia da Saúde Program, created by the Health Surveillance Secretariat of the Ministry of Health from 2005 onwards. Patients with obesity are developed in Basic Health Units as a way to adequately monitor the progress of obesity and other diseases that accompany it.